Uji Kelayakan: E-Modul Praktikum Intersktif Berbasis PBL untuk Meningkatkan Critical Thinking - Haresda Varentine; Arini Rosa Sinensis; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2024)
The changes of the 4.0 revolution era explicitly impact educational patterns, particularly in learning outcomes that emphasize the achievement of 4Cs skills. (critical thinking, communication, collaboration, creativity). The need for suitable teaching materials is a fundamental aspect of implementing better learning. This research was conducted to develop an interactive practical E-module based on PBL for uniformly accelerated motion (GLBB) that is suitable for fostering Critical Thinking. The method used to test the feasibility of the products produced in this research is through justice expert assessments to obtain feedback and evaluations from experts in content, media, and language regarding the research product. The feasibility of the practical E-module, based on justice expert evaluations from content, language, and media, has holistic Aiken indices of 0.873, 0.729, and 0.781, respectively. This can mean that the product meets the criteria of being very valid and valid. The results of the requirements on the research product can undergo feasibility and effectiveness testing